Dual Antegrade Intramedullary Headless Screw Fixation for Treatment of Unstable Proximal Phalanx Fractures. (July 2019) - Gaspar, Michael P.; Gandhi, Shiv D.; Culp, Randall W.; Kane, Patrick M.
Background: Although intramedullary headless screw (IMHS) fixation is a promising minimally invasive surgical treatment option for unstable proximal phalanx fractures, a single IMHS may provide inadequate fixation for certain fracture patterns. The purpose of this study was to evaluate the short-term clinical outcomes in a pilot series of patients with proximal phalanx fractures treated with dual antegrade IMHS fixation.Methods: We performed a retrospective chart review of proximal phalanx fractures treated with dual antegrade IMHS fixation with a minimum 1 year of follow-up. Demographic information including patient age, sex, occupation, workers' compensation status, mechanism of injury, hand dominance, and injured digit were obtained. Postoperative outcomes measured included range of motion, grip strength, Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) outcome scores, return to full-duty work interval, and complications.Results: Ten fractures in 10 patients (4 male, 6 female) satisfied study inclusion. The mean age of patients was 39 years (range, 20-62), and average follow-up duration was 84 weeks (range, 61-106). Final postoperative total active motion was 258° (range, 245°-270°), mean grip strength was 97% (range, 84%-104%) of the uninjured side, and QuickDASH score was 3.9 (range, 0-13.6). No complications occurred, and no patients required additional intervention.Conclusions: Dual antegrade IMHS fixation of proximal phalanx fractures resulted in excellent postoperative motion, near-normal grip strength, positive self-reported patient outcomes, and no complications with follow-up of at least 1 year. Further study in a larger number of patients is warranted to determine if this promising technique is superior to other modes of fixation.